Asymmetric synthesis of (S)-vigabatrin (R) and (S)-dihydrokavain via cobalt catalyzed hydrolytic kinetic resolution of epoxides - Raj, I. Victor Paul; Sudalai, A. (Tetrahedron Letters, 2008)
A concise route to the asymmetric synthesis of (S)-vigabatrin(R) and (S)-dihydrokavain has been described using Co-catalyzed hydrolytic kinetic resolution of racemic epoxides and regiospecific opening of terminal epoxides with dimethylsulfonium methylide as the key steps. (C) 2008 Elsevier Ltd. All rights reserved.